Once upon a time in Africa : Stories of Wisdom & Joy - Healey, Joseph G. (New York Orbis Books, 2004)
This rich collection of nearly a hundred stories from every part of Africa--legends and folktales, myths and parables, poems, prayers and proverbs--probes deeply into the heart and our relationships with God and one another.
Keywords: Tham khảo